The Effect Of Transformational Leadership And Perceived Organizational Support On Innovative Performance Behavior Mediated By Work Engagement - Imam Syabudin Anwar; Lie Liana (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of transformational leadership and perceived organizational support on innovative performance behavior mediated by work engagement. This study used a quantitative approach with a population of 2,523 Pekalongan City Government ASN employees as of October 2025. The sample size was calculated using the Slovin formula and obtained a sample size of 110 employees. Sampling was conducted using a purposive sampling technique with the following criteria:years of serviceThe respondents had a minimum of 3 years of experience so that they had sufficient work experience to feel the influence of leadership and perceived organizational support on innovative work behavior. The data were processed using SPSS software version 26. Data analysis techniques included respondent descriptions, variable descriptions, validity tests, reliability tests, F tests, R2 tests, t tests, and Sobel tests. The results of the study stated that transformational leadership had a positive effect on work engagement, perceived organizational support had a positive effect on work engagement, transformational leadership had no effect on innovative work behavior, perceived organizational support had no effect on innovative work behavior, work engagement had a positive effect on innovative work behavior, work engagement mediated the effect of transformational leadership on innovative work behavior, and work engagement mediated the effect of perceived organizational support on innovative work behavior.